Understanding Barriers to Continuous Ambulatory Peritoneal Dialysis: A Qualitative Study from Health Professionals’ Perspectives - Fitri Mailani; Emil Huriani; Yevri Zulfiqar; Rahmiwati; Setiawan (Caring: Indonesian Journal of Nursing Science, 2025)
The declining number of end-stage renal disease (ESRD) patients who opt for Continuous Ambulatory Peritoneal Dialysis (CAPD) as a renal replacement therapy is influenced by several factors, including high infection rates, limited patient and family knowledge, and restricted access to CAPD services. However, research exploring the perspectives of healthcare professionals, such as dialysis nurses and nephrologists, on this phenomenon remains limited. This study aimed to explore the perspectives of dialysis nurses and nephrologists regarding barriers to CAPD utilization. A qualitative descriptive design was employed, using semi-structured interviews with 12 participants, including 10 dialysis nurses and 2 nephrologists at a tertiary hospital in West Sumatra, Indonesia. Data were analyzed using Colaizzi’s seven-step method. Five major themes emerged: (1) Weak coordination, unsupportive policies, and limited expertise; (2) Infection risk as the primary challenge in CAPD; (3) Ineffective patient and family education in CAPD care; (4) Psychological barriers to accepting CAPD therapy; and (5) Determinants of patient decision-making in choosing CAPD, and 15 Sub-themes. This study highlights the barriers that patients face when choosing CAPD as a renal replacement therapy. Unsupportive policies, increased infection risks, and inadequate educational systems were identified as key challenges that require urgent evaluation and improvement. Strengthening these aspects is crucial to ensure optimal care for patients who opt for CAPD. Keyword: Indonesia, Nephrologist, Nurse Perspective, Peritoneal Dialysis, Qualitative Study